2010
DOI: 10.1007/s00125-010-1803-z
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis model assessment of insulin resistance and the risk of cardiovascular events in middle-aged non-diabetic Japanese men

Abstract: Increased HOMA-IR predicted subsequent cardiovascular events in non-diabetic Japanese men. The association was independent of traditional cardiovascular risk factors and other relevant metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
1
39
0
1
Order By: Relevance
“…The present study demonstrated positive relationship between HOMA-IR and ischemic stroke in non-diabetic patients adjusting for traditional risk factors for stroke, which is similar to the studies done by Rundek [6] in western population and Nakamura et al [13] in Asians and in Bruneck study [14]. This finding suggests that IR has alternative pathways directly related to inflammation, atherosclerosis and stroke and IR is considered an important independent marker of stroke risk.…”
Section: Discussionsupporting
confidence: 79%
“…The present study demonstrated positive relationship between HOMA-IR and ischemic stroke in non-diabetic patients adjusting for traditional risk factors for stroke, which is similar to the studies done by Rundek [6] in western population and Nakamura et al [13] in Asians and in Bruneck study [14]. This finding suggests that IR has alternative pathways directly related to inflammation, atherosclerosis and stroke and IR is considered an important independent marker of stroke risk.…”
Section: Discussionsupporting
confidence: 79%
“…Mounting evidence from the last years supports the importance of the HOMA-IR index as a prognosticator even at values very close to the normal range, i.e., in patients not fitting a diagnosis of T2D. Recent studies demonstrated its independent value in the prediction of CV events in the general adult non-diabetic population [12,13] . In light of these epidemiological findings, our results appear strengthened in their clinical significance, strongly advocating further research in the field.…”
Section: Discussionmentioning
confidence: 98%
“…There is still no clear cutoff for the definition of insulin resistance based on HOMA-IR, and Japanese subjects have lower levels of HOMA-IR and lower insulin secretion than Western subjects (26,27). A recent prospective study showed that even minimal increases in HOMA-IR levels predicted subsequent cardiovascular events in non-diabetic Japanese men (28). These findings suggest that the HOMA-IR cutoff value proposed by this study may have clinical implications for type 2 diabetes and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 60%